Impact of hexavalent chromium, a lung carcinogen, on the stress response of cultured human epithelial cancer cells and on their susceptibility to stress - Rosa, Inês de Carvalho Fresco da (2022)
Dissertação de Mestrado em Bioquímica apresentada à Faculdade de Ciências e Tecnologia